DESKRIPSI KINERJA PAMONG DI SANGGAR KEGIATAN BELAJAR (SKB) KABUPATEN LIMA PULUH KOTA - Titi Mutiah Hanifah (Universitas Negeri Padang, 2015)
The backgrround of this research is by SKB success in carrying out the activities. This is presumably because the performen of pamong SKB. The purpose of this research is to describe the performance of work discipilin of pamong, work ability of pamong and work responsibilities of pamong. The type of this research is descriptive quantitative research. Population in this research were all of Pamong SKB Kabupaten Lima Puluh kota. With a population of 15 people. From the results can be seen that the description of the performence of pamong SKB terms of (1) work disciplin of Pamong can be said is good, (2) the ability of the pamong can be said is good.(3) work responsibilities of pamongS can be said is good.Keywords: Disciplin,Ability, And Responsible.